Effects of stably incorporated iron on protein phosphatase-1 structure and activity - Salvi, Francesca; Hoermann, Bernhard (FEBS letters, 2018)
Protein phosphatase-1 (PP1) drives a large amount of phosphoSer/Thr protein dephosphorylations in eukaryotes to counteract multiple kinases in signaling pathways. The phosphatase requires divalent metal cations for catalytic activity and contains iron naturally. Iron has been suggested to have an influence on PP1 activity through Fe2+ and Fe3+ oxidation states. However, much biochemical and all structural data have been obtained with recombinant PP1 containing Mn2+ ions. Purifying iron-containing PP1 from Escherichia coli has thus far not been possible. Here, we present the preparation, characterization, and structure of iron-bound PP1α in inactive and active states. We establish a key role for the electronic/redox properties of iron in PP1 activity and shed light on the difference in substrate specificity between iron- and manganese-containing PP1.